Formação de filme polimérico derivado de ácido 3-hidroxifenilacético para a construção de biosensores - Oliveira, Ronalt Marcelino Lemos de (2010)
A polymer derived from 3-hydroxi phenyl acetic acid, poly-(3-HFA) was produced over a graphite electrode in an aqueous acid media through cyclic voltammetry with the intention to form an interface for biomolecule detection for a biosensor development. Cyclic voltammograms show that electropolymerization process begins around +0.9V, with the appearance of an oxidation wave reaching a peak potential at +1.06V. This wave is pointed as being the monomer oxidation for its cation-radical form. With a second cycle there is a current values decrease of this wave and a redox pair waves appears between +0.3 and +0.7V. This pair refers to the redox process of the polymeric film, growing over the electrode surface. As the sweep number increases it is observed a large current values increase of these redox waves, pointing the formation of electroactive material with a low insulating behavior. The electrical properties of this polymer were determined through electrochemical impedance spectroscopy (EIS) and the electrochemical quartz crystal microbalance (EQCM). high frequency and another in low frequency ranges, suggesting the existence of two time constants, which can be confirmed through Bode diagram. This result suggest that the poly-(3- HFA) electrochemical behavior is controlled by kinetic processes in high frequency ranges and by mass transport in low frequency ranges. The obtained result were simulated by a set of physical resistances and capacitances to fit to the experimental data, seeking the better circuit to represent it, which the first time constant is referred to an electronic transference on the electrode surface between the polymer and the solution and the second refers to mass transport processes in poly-(3-HFA) inner layers. For the EQCM result, it is observed that the charge/frequency profile present a linear behavior, namely, a rigid film is being deposited over the electrode surface and the Sauerbrey equation is valid for the mass calculus. It is observed that, on the first cycle, the mass values remained constant until around +0.9V, exactly where the electropolymerization process begins. After 1.0V, the monomer, reaching its oxidation potential, begins to form the cation-radical structures which adsorbs on the electrode proved by the mass values increase. During the reverse potential sweep, there is an additional mass increase due to the part of the monomer oxidation over this range. After this point, a little mass values decrease is observed, however, remaining constant until the end of the cycle.